Development of Ethnomathematical Media Based on the Book Creator Application on the Syawalan Tradition in the Junior High School Curriculum - Rani Darmayanti; Muhammad Mahfud Effendi; Niswatun Hasanah; Akhsanul In'am (AL-ISHLAH: Jurnal Pendidikan, 2022)
Culture-based learning enables teachers and students to participate actively based on their knowledge about culture, producing optimal learning results. Ethnomathematics, particularly math, is a potential bridge gap Between culture and education. Because of that's very important to plan appropriate teaching materials in Pasuruan with characteristics of learning mathematics-based ethnomathematics in traditional syawalan. Study this aim for make product in the form of a book -based creator ethnomathematics in understand draft for could complete problem mathematics, as well knowing response and results in study student after using learning media on the material algebra. The techniques used are descriptive and qualitative using ethnomathematics e-books. The development used a 4D model consisting of 4 stages: definition, design, development, and stage dissemination. Instruments used shaped responses students through sheet questionnaires and test results studied through sheet tests. Based on validity test analysis by (media, materials, and experts culture), practicality test through response student gets average score 3.62 with category excellent practicality, effectiveness test, and analysis ability understanding draft student through test understanding completeness study by 82 percent. So that could conclude that the developed ethnomathematical e-book media in traditional syawalan "lontong vegetables” for increase understanding draft middle school students about operation algebra worthy used to enhancement understanding draft students because of Fulfill valid, practical, and effective criteria.